ADMINISTRATIVE PROCEDURES FOR MANAGEMENT AND SECURITY OF INVENTORY OF GOODS - Syamsul Arifin; Lis Setyowati; Komarun Zaman; Nur Aini Anisa (CV Pena Jaya Pers, 2024)
This study aims to describe the analysis of administrative procedures for managing and securing inventory in the finished goods warehouse at PT. Aidai Indonesia Jaya. The data studied is in the form of finished goods inventory management reports for PT. Aidai Indonesia Jaya. The data collection technique used is documentation technique. The data analysis technique used is a qualitative descriptive analysis technique.The results of this research indicate that inventory management must be very careful regarding data and physical stock. Using a custom system that has been structured in accordance with company procedures. Checking physical stock of goods and matching item data is important to achieve the desired goals. Securing goods is also something that needs to be considered to avoid theft and disputes. The benefit of regular checking and checking of stock is to provide relevant data and the company's sales will be well controlled.